An examination of the effect of loan interest rates to smes’ performance and growth in Tanga City: A case of vision fund Tanzania - Msangula, Leah Yesaya (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for award of the degree of Masters of Business Administration in Corporate Management (CM) of Mzumbe University